2013
DOI: 10.1534/g3.113.007021
|View full text |Cite
|
Sign up to set email alerts
|

FlyPrimerBank: An Online Database for Drosophila melanogaster Gene Expression Analysis and Knockdown Evaluation of RNAi Reagents

Abstract: The evaluation of specific endogenous transcript levels is important for understanding transcriptional regulation. More specifically, it is useful for independent confirmation of results obtained by the use of microarray analysis or RNA-seq and for evaluating RNA interference (RNAi)-mediated gene knockdown. Designing specific and effective primers for high-quality, moderate-throughput evaluation of transcript levels, i.e., quantitative, real-time PCR (qPCR), is nontrivial. To meet community needs, predefined q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
109
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(109 citation statements)
references
References 34 publications
0
109
0
Order By: Relevance
“…For the selected reference genes (α-Tub84b, eif-1a, and CG13220), we next confirmed that the presence plot for each gene matched its corresponding FlyBase model (St Pierre et al 2014). We then selected primers using FlyPrimerBank (Hu et al 2013) and relevant publications (Ling and Salvaterra 2011) and optimized them for qRT-PCR.…”
Section: Reference Genesmentioning
confidence: 63%
See 1 more Smart Citation
“…For the selected reference genes (α-Tub84b, eif-1a, and CG13220), we next confirmed that the presence plot for each gene matched its corresponding FlyBase model (St Pierre et al 2014). We then selected primers using FlyPrimerBank (Hu et al 2013) and relevant publications (Ling and Salvaterra 2011) and optimized them for qRT-PCR.…”
Section: Reference Genesmentioning
confidence: 63%
“…For primer optimization (Eurofins MWG Operon), we produced standard curves using at least five 1:5 dilutions of RNA starting at 50 ng cDNA. Primer sequences were taken from FlyPrimerBank and citations (Ling and Salvaterra 2011;Hu et al 2013). Gene names, primer sequences, amplicon length, efficiency, R 2 of primers are given in Supplemental Table S9.…”
Section: Qrt-pcrmentioning
confidence: 99%
“…RT-qPCR was performed using QScript XLT 1-step RT-qPCR ToughMix (Quanta Biosciences) on a CFX96 Touch RealTime PCR Detection system (Bio-Rad) with a commercially designed primer and probe assay (TaqMan Gene Expression Assays, Life Technologies). Alternatively, first-strand cDNA was synthesized with random nonamer primers before qPCR using iQ SYBR Green Supermix (Bio-Rad), as described previously (66), and predefined primer pairs from FlyPrimerBank (67). Relative gene expression was calculated using the ΔΔCt method (68) and normalized to total input RNA.…”
Section: Methodsmentioning
confidence: 99%
“…On average, 65% of TRiP stocks display knockdown efficiencies of .50% ( Figure 6A). To facilitate searching for primers appropriate for RT-qPCR analysis, we assembled FlyPrimerBank (http://www.flyrnai.org/ FlyPrimerBank) (Hu et al 2013b). Relevant to long dsRNA reagents, the tool indicates if a given primer pair should be avoided as the primers are predicted to amplify the dsRNA itself.…”
Section: Validation Of the Trip Linesmentioning
confidence: 99%